Analisis Pendapatan dan Pola Pengeluaran Rumah Tangga Miskin Di Kabupaten Sarolangun - Bahrun Bahrun; Syaparuddin Syaparuddin; Hardiani Hardiani (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2014)
The purpose of the research entittled ’An Analysis of Income and Expenditure Patterns of the Poor Households di Sarolangun Regency’, they are: First, to analyze the poor households income in Sarolangun Regency. Second, to analyze the education level of the poor households in Sarolangun Regency. Third, to analyze the expenditure pattern of the poor households in Sarolangun Regency. Forth, to analyze the poor households income’s inequality in Sarolangun Regency. The result of the research shows that, First; the monthly average of poor households income in Sarolangun Regency is Rp.852.057,- each family. Second, in the education level point of view, 90,6% of the poor household only completed their Elementary School. Third, in the expenditure-pattern point of view, in average, the expenditure-pattern of 72,96% poor households in Sarolangun Regency spent their income in food consumption, other 12,07% spent their income in primary needs (electricity, gas, water) and the rest 14,97% for vary. It is indicate that the expenditure pattern of poor households in Sarolangun Regency still concern to the primary consumption. Fourth, the poor households income’s inequality in Sarolangun Regency in average is 0,30. Keywords: primary need, expenditure pattern, income’s inequality